2018
DOI: 10.1242/jeb.170753
|View full text |Cite
|
Sign up to set email alerts
|

Detection and direction discrimination of single vortex rings by harbour seals (Phoca vitulina)

Abstract: Harbour seals possess highly sensitive vibrissae that enable them to track hydrodynamic trails left behind by a swimming fish. Most of these trails contain vortex rings as a main hydrodynamic component. They may reveal information about their generator as the trails differ depending on the fish species, the fish's body shape, size and swimming style. In addition, fish generate single vortex rings in diverse natural situations. In this study, the ability of blindfolded stationary harbour seals to detect and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 48 publications
(50 reference statements)
1
30
0
Order By: Relevance
“…Summarell et al (2015) found that smooth whiskers were stiffer than undulating whiskers. Since phocids, with undulating whiskers, tend to be better at hydrodynamic tasks (Gläser et al, 2011; Hanke et al, 2013; Krüger et al, 2018; Niesterok et al, 2017), the authors suggest that having some flexibility of the whiskers might be useful for hydrodynamic sensing in phocids, while stiffer whiskers might be better for touch sensing in otariids. While we suggest here that aquatic mammal whiskers are stiffer than those of terrestrial mammals, for otariids and phocids, a more complex three‐dimensional approach may be needed in order to fully compare whisker stiffness between these species, especially to better understand the functional significance of whisker stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Summarell et al (2015) found that smooth whiskers were stiffer than undulating whiskers. Since phocids, with undulating whiskers, tend to be better at hydrodynamic tasks (Gläser et al, 2011; Hanke et al, 2013; Krüger et al, 2018; Niesterok et al, 2017), the authors suggest that having some flexibility of the whiskers might be useful for hydrodynamic sensing in phocids, while stiffer whiskers might be better for touch sensing in otariids. While we suggest here that aquatic mammal whiskers are stiffer than those of terrestrial mammals, for otariids and phocids, a more complex three‐dimensional approach may be needed in order to fully compare whisker stiffness between these species, especially to better understand the functional significance of whisker stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Pinniped whiskers, in particular, have been studied, due to their prominence, high sensitivity (Hyvärinen and Katajisto 1984;Hyvärinen 1989;Dehnhardt et al 1998;Mauck et al 2000;Marshall et al 2006;Hyvärinen et al 2009;Erdsack et al 2014;McGovern et al 2014) and their ability to be moved using a network of voluntary muscles (Berta et al 2005). Indeed, Pinniped whiskers are capable of the tactile discrimination of object textures, shapes and sizes to a similar sensitivity as human fingertips (Dykes 1975;Murphy et al 2015) and can also detect fine-scale water movements, termed hydrodynamic sensing (Dehnhardt et al 2001;Wieskotten et al 2010a, b;Krüger et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Harbour seals (Phoca vitulina) detect and analyse subsurface water motions not only of the sinusoidally oscillating dipole type (Dehnhardt et al 1998a), which bear some resemblance with the water movements generated by oscillating body parts, but also direct current water jets (Wieskotten et al 2011;Niesterok et al 2017a, b;Krüger et al 2018). Direct current water jets occur, for example, in the tail wake of fishes (Hanke and Bleckmann 2004;Niesterok and Hanke 2013), where they often form the central part of vortex rings, and in the breathing currents of fishes (Niesterok et al 2017b).…”
Section: Sensitivity To Horizontal Water Motionsmentioning
confidence: 99%
“…Direct current water jets occur, for example, in the tail wake of fishes (Hanke and Bleckmann 2004;Niesterok and Hanke 2013), where they often form the central part of vortex rings, and in the breathing currents of fishes (Niesterok et al 2017b). As vortex rings produced by fish tails constitute strong and stable flow structures, they appear to be promising subjects for future studies on the discrimination and directional sensitivity of Hydromys to hydrodynamic stimuli, corresponding to studies on stationary harbour seals (Krüger et al 2018).…”
Section: Sensitivity To Horizontal Water Motionsmentioning
confidence: 99%